Journeys into the Rainforest (Terra Australis 43) - Ferrier, Åsa (ANU Press, 2016)
This monograph presents the results of archaeological research that takes a longitudinal approach to interpreting and understanding Aboriginal-European contact. It focuses on a small but unique area of tropical rainforest in far north Queensland's Wet Tropics Bioregion, located within the traditional lands of the Jirrbal Aboriginal people on the Evelyn Tableland. The research integrates a diverse range of data sources: archaeological evidence recovered from Aboriginal open sites occupied in the pre- to post-contact periods, historical documents of early ethnographers, settlers and explorers in the region, supplemented with Aboriginal oral history testimony. Analyses of the archaeological evidence excavated from three open sites facilitated the identification of the trajectories of culture change and continuity that this investigation focused on: Aboriginal rainforest material culture and technology, plant subsistence strategies, and rainforest settlement patterns. Analyses of the data sets demonstrate that initial use of the rainforest environment on the Evelyn Tableland occurred during the early Holocene period, with successful adaptation and a change towards more permanent Aboriginal use of the rainforest becoming established in the late Holocene period. European arrival and settlement on traditional Aboriginal land resulted in a period of historical upheaval for the Aboriginal rainforest people. Following an initial period of violent interactions and strong Aboriginal resistance from the rainforest, Jirrbal Aboriginal people continued to adapt and transform their traditional culture to accommodate for the many changes forced upon them throughout the post‑contact period.